THE HAZARD TOWARD NATURE IN WILLIAM STANLEY MERWIN’S POEM COLLECTION (2010); THE CHAIN IN HER LEG, IDENTITY, SHORE BIRD, UNKNOWN BIRD, THE OTHER TREE - Yoffi Boni Adha'fri; An Fauzia Rozani Syafei (English Language and Literature, 2019)
This study is aimed to expose the issue about the hazard toward nature which is done by human through poetic elements and figurative language; speaker, imagery and symbol in revealing the hazard toward nature. This analysis related to concept of eco-criticism by Kent Rayden, Barry and Ikkiara. The result of this analysis shows that the hazard toward nature is done in two ways; animal abuse and deforestation.